Poisoned politics ebook - Sefton, Maggie (Molly Malone Mystery, 2013)
The second book in New York Times bestselling author Maggie Sefton's dazzling political mystery series Beltway doyenne Samantha Calhoun has learned many lessons in a lifetime of politics, and she relishes teaching certain young congressmen everything she knows. But when her latest fling, married U.S. Rep. Quentin Wilson, is found dead in Samantha's home, she turns to longtime friend Molly Malone for support. Putting to use her many well-positioned connections, Molly learns that Wilson had been researching a financial bill sponsored by a veiled coalition of politicians—the same bill that her niece Karen Grayson was investigating when she was murdered. Picking up the trail where Grayson and Wilson left off, Molly fears she will be the next victim of the shadowy cabal's insatiable appetite for power. Praise for Deadly Politics: "Sefton has a sharp ear for dialog and knack for writing strong female characters."— Library Journal